Dampak Artificial Intelligence Dalam Pembelajaran Matematika Di Era Society 5.0. - Amelia Kusuma Wardhani; Felisa Okta Amelin; Arifta Nurjanah; Reyhan Hana Dwi Putra (JURNAL PENELITIAN PENDIDIKAN MATEMATIKA DAN SAINS, 2025)
The development of Artificial Intelligence (AI) technology in the Society 5.0 era presents both opportunities and challenges for mathematics learning. Although AI can improve motivation, conceptual understanding, and provide more adaptive learning, various findings indicate the risk of student dependence on technology, which can potentially reduce critical and creative thinking skills. This study aims to examine the impact of AI use in mathematics learning, focusing on the phenomenon of dependence and its influence on the thinking process. The method used was a literature review through searching articles from Google Scholar and selecting based on relevance to the topic. Five articles were analyzed to identify patterns of benefits, challenges, and risks of using AI in the context of mathematics education. The results of the study indicate that AI is effective in increasing efficiency, personalization, and learning engagement. However, excessive use without pedagogical supervision can reduce students' analytical, evaluation, and creativity skills. These findings emphasize the importance of wisely integrating AI with the support of digital literacy, the active role of educators, and clear regulations. This study is expected to provide a basis for consideration in developing mathematics learning strategies that balance the use of technology and strengthening higher-order thinking skills.